THE EFFECT OF Moringa oleifera LEAF EXTRACT ON THECA CELL IN POLYCYSTIC OVARY SYNDROME MODEL WITH INSULIN RESISTANCE - Lisa Purbawaning Wulandari; Anindya Hapsari (Jurnal Kedokteran Hewan, 2020)
The use of Moringa oleifera as an anti-oxidant should be investigated as an alternative treatment of follicular refinement in Polycystic ovary syndrome (PCOS) with insulin resistance. We aimed to prove the effect of Moringa oleifera leaf extract in various dosages to decrease the thecacell thickness of PCOS female rat with insulin resistance. This study was a laboratory experimental research. Three month old Rattus norvegicusstrain Wistar rat weighing 100-130 g were divided into 5 groups (n= 8). PCOS model obtained by giving injection of testosterone propionate for28 days, followed by metformin therapy and Moringa oleifera leaf extract at 250 and 500 mg/kg BW for 14 days. The examination of ovariumhistology showed that leaf extract Moringa oleifera 500 mg/kg BW (0.931±0.457) significantly decreased the thickness of theca cells (P0.05)compared to the PCOS control group. The conclusion was Moringa oleifera leaf extract as an anti-oxidant proven to decrease the thickness oftheca cell of the female rat model of PCOS.